If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (k + 5)(k + -1) = -8 Reorder the terms: (5 + k)(k + -1) = -8 Reorder the terms: (5 + k)(-1 + k) = -8 Multiply (5 + k) * (-1 + k) (5(-1 + k) + k(-1 + k)) = -8 ((-1 * 5 + k * 5) + k(-1 + k)) = -8 ((-5 + 5k) + k(-1 + k)) = -8 (-5 + 5k + (-1 * k + k * k)) = -8 (-5 + 5k + (-1k + k2)) = -8 Combine like terms: 5k + -1k = 4k (-5 + 4k + k2) = -8 Solving -5 + 4k + k2 = -8 Solving for variable 'k'. Reorder the terms: -5 + 8 + 4k + k2 = -8 + 8 Combine like terms: -5 + 8 = 3 3 + 4k + k2 = -8 + 8 Combine like terms: -8 + 8 = 0 3 + 4k + k2 = 0 Factor a trinomial. (3 + k)(1 + k) = 0Subproblem 1
Set the factor '(3 + k)' equal to zero and attempt to solve: Simplifying 3 + k = 0 Solving 3 + k = 0 Move all terms containing k to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + k = 0 + -3 Combine like terms: 3 + -3 = 0 0 + k = 0 + -3 k = 0 + -3 Combine like terms: 0 + -3 = -3 k = -3 Simplifying k = -3Subproblem 2
Set the factor '(1 + k)' equal to zero and attempt to solve: Simplifying 1 + k = 0 Solving 1 + k = 0 Move all terms containing k to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + k = 0 + -1 Combine like terms: 1 + -1 = 0 0 + k = 0 + -1 k = 0 + -1 Combine like terms: 0 + -1 = -1 k = -1 Simplifying k = -1Solution
k = {-3, -1}
| 3p^3-75p=3p^2-75 | | 10x+5=23 | | 3z^4=3z^2 | | x^4+28=11x^2 | | 2b+3a= | | 9x+30=2x^2 | | 9c+6= | | 5x+5x=20 | | Log[5](6x+1)=2 | | 15-2=52x | | (7x^2-4x-5)+(6x^2-x+2)= | | 3(-1x-3)=0 | | 6(-7x+5)=30 | | x*2+4x-1=0 | | 4(10-5x)=0 | | 5(7+3x)=-100 | | -5(5x-10)=325 | | -2(2-4x)=52 | | 2(u-2)=9u+8-2(-4u-3) | | f(x)=1.2 | | -7+4x=-4x-95 | | 4x+5y=28.50 | | y-3=5(x-6) | | 8v-5v-2v=17 | | -2x+6=4x+6 | | -7(x+4)-18=15+2 | | 160=(x)(16-x)+x | | P(x)=-250x^2+125x | | m+12+4m=21 | | -x-7=-4x-43 | | 3v+9+v=19 | | v+8+3v=20 |